SOBAMA - THE ART OF GROUPING - Cidade, Ruth Eugênia (UNESP, 2021)
This article refers to a commemorative edition of the Brazilian Society of Adapted Motor Activity. Some ideas are presented here regarding the mobilization and grouping of professionals in the field. The essential points in relation to the mobilization and grouping of professionals were made concrete at the Sobama congresses and today on the homepage of the Brazilian Association of Adapted Motor Activity.